A Study on the Effect of COVID-19 on the Lifestyle & Mindset of People after Lockdown in Gujarat State - Komal K.Shukla; Prof.(Dr.) Darshana R.Dave; Dr. Shivangi K.Shukla (International Journal of Engineering and Management Research, 2021)
This study aimed to research the immediate impact of the COVID-19 pandemic on psychological state and quality of life among Gujarat resident’s aged ≥18 years. a web survey was distributed through a social media platform from May 19, 2020 to May 22, 2020. Respondents completed a validated questionnaire that assessed the indications of mindset impacts, social and family support, and mental health-related lifestyle changes. a complete of 150 respondents (87 males and 63 females) completed the study Around 26% of the respondents believe that the lockdown 4.0 should be lifted fully. 56% prefer to stay at home even after lockdown lifted fully. Very few 5% around prefer to travel after lockdown 4.0. When there was a lockdown curfew, people were having different kind of stress. Majority of the people were having stress of getting corona virus. Some respondents were having stress related to their loss of job or pay cut. People tried to stay positive and did prayer to come out of the stress during lockdown period. 51% of the respondents said that they would like to prefer to go to the different public places after 3 months of lockdown 4.0. Majority of the respondents are having a positive attitude towards their lifestyle after COVID -19. People before COVID- 19 were very much socialized and not that much caring for their body. Now, people after COVID – 19 are more aware about their immunity, health, lifestyle and mental health as well. Of course, there is a change in everyone’s lifestyle and thinking. And this will bring something positive. In conclusion, the COVID-19 pandemic was associated with mild stressful impact in our sample, even though the COVID-19 pandemic is still ongoing.